Preparation and performance for CO2 adsorption of large‐scale microporous fiber membrane based on electrostatic spinning technology. Issue 30 (21st May 2022) - Ran, Hongshun; Yan, Wenhui; Tan, Wenze; Hu, Zhixin; Huang, Changxin; Yang, Shigang; Yuan, Zixi; Chen, Xueqin; Li, Cao; Xu, Ziqiang; Jiang, Bingbing
Abstract: Although nano‐porous materials are widely used, they are still difficult to prepare in large size and expand flexibly. In this work, a new method for the synthesis of porous materials is proposed. First, the block polymers were prepared by atom transfer radical polymerization. Through electrostatic spinning, the fiber films were fabricated, then the fibers were modified by surface post‐treatment and related Friedel–Crafts alkylation reaction. The pore and CO2 adsorption properties of the porous fiber films are characterized by nitrogen adsorption–desorption isotherm. In order to improve the pore properties and CO2 adsorption properties of thin films, the additives and pretreatment process are optimized. The maximum specific surface area of the porous fiber membrane is determined to be 640 m 2 /g, and the CO2 adsorption capacity is high up to 36.3 wt.% (8.68 mmol/g). Moreover, the porous fiber membrane derived from this strategy is superior in the aspects of large size, convenient adjustment and simple processing, which makes up for the drawbacks of traditional porous materials. The fiber membrane obtained by this strategy has high productivity, and the fiber membrane is easy to be postprocessed, which can be integrated into functional devices, and is widely used. Abstract :